I dressed her up in her best dress: The experiences of the dead body for bereaved relatives in the context of palliative care - J. Mowll; K. Bindley; E.A. Lobb; C. Sanderson; R.M. MacLeod (Elsevier, 2022)
Critical exploration of family members' experience of the body of their deceased relative after a death in palliative care have been limited. To address this gap, we drew on semi-structured interviews at 6 months post loss with 58 family members bereaved after a death in palliative care, as part of a larger, longitudinal study conducted between 2016 and 2018. Narrative thematic analysis elucidated themes within and across participants' accounts of their experiences of the body. Social constructionist perspectives underpin recognition of the processes of grieving family members. Within an overarching theme of social meanings of the dead, five themes pertained to individual, relational, and contextual dimensions of interactions with the body, including: a dual sense of the body still holding the person and as just a body; family's experiences of the body both at home and in formal care settings; expectations around the right amount of time to be with and leave the body. Accounts also revealed their sense of knowing or not knowing what to do with the dead and elements of preparation of the body and management of the family and body by professional caregivers, with differences for deaths at home and deaths in formal settings. Findings highlight the importance of facilitating family and individual preferences, and options around care, place, and time with the body. Focus on support from clinical and social work staff, is warranted to enable provision of informed choice and support for families to engage with the body. Challenges related to COVID-19 are discussed.